2017
DOI: 10.21763/tjfmpc.359842
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Related Factors in Medical Residents

Abstract: Introduction: The aim of this study was to assess the sleep quality and daytime sleepiness of resident doctors, to compare the sleep quality between surgical and medical branch residents and to examine effects of working hours, number of duties, clinical branches and some other daily habits on the sleep quality of resident doctors in a hospital in Turkey. Methods: A survey was conducted to gather data on (i) demographics, lifestyle and daily habits as well as to determine (ii) Epworth sleepiness scale (ESS) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“… 32 In addition, a high frequency of on-call shifts per month (more than six) was significantly associated with a 10-times greater risk of poor sleep quality.Similarly, several previous studies have shown an inverse relationship between sleep quality and the number of monthly on-calls, illustrating the impact of night shifts on residents’ sleep. 30 , 33 Residents in dermatology and psychiatry departments reported the highest prevalence of adequate sleep quality compared with other, mostly surgical specialties, consistent with previous findings. 12 This could be related to the stressful lifestyle inherent to surgical training, where emergencies are abundant, work hours are longer, and caffeine intake is higher.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 32 In addition, a high frequency of on-call shifts per month (more than six) was significantly associated with a 10-times greater risk of poor sleep quality.Similarly, several previous studies have shown an inverse relationship between sleep quality and the number of monthly on-calls, illustrating the impact of night shifts on residents’ sleep. 30 , 33 Residents in dermatology and psychiatry departments reported the highest prevalence of adequate sleep quality compared with other, mostly surgical specialties, consistent with previous findings. 12 This could be related to the stressful lifestyle inherent to surgical training, where emergencies are abundant, work hours are longer, and caffeine intake is higher.…”
Section: Discussionsupporting
confidence: 88%
“… 12 This could be related to the stressful lifestyle inherent to surgical training, where emergencies are abundant, work hours are longer, and caffeine intake is higher. 33 In our institution, dermatology residents have no on-calls except in the first year, and psychiatry residents tend to have more quiet and less busy on-calls than other departments.…”
Section: Discussionmentioning
confidence: 94%
“…The analyzes were conducted with the Statistical Package for Social Sciences (SPSS Inc., Chicago, IL) v. 22…”
Section: Discussionmentioning
confidence: 99%
“…19,20 It was found that the mean PSQI score was higher in night shift workers or college students who attended non-formal education. [21][22][23] It could be suggested that the differences determined in the present study was due to the fact that certain students attended non-formal education. In the present study, the rate of poor sleep quality of those who attended non-formal education was significantly higher than those who received formal education.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition and management of fatigue are very important. [15][16][17][18][19] This research shows that there is a positive relationship between anxiety and sleep quality. This is similar to previous research on the relationship between anxiety levels and sleep quality in 278 medical students at the undergraduate, graduate, and doctoral levels.…”
Section: Journal Of Clinical and Cultural Psychiatry 07mentioning
confidence: 99%